PRIORITY HEALTH PROBLEM ANALYSIS WITH BPRS AT MAGETAN HEALTH OFFICE IN 20202 - Khofifah, Nurul Alif (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2025)
Background: Health issues significantly impact a country's development, and high disease incidence and inadequate handling contribute to these challenges. Determining health priorities can be achieved through various methods, including the Basic Priority Rating System (BPRS), also known as the Hanlon method. Objective: This research aims to identify health problems and suitable solutions using the BPRS method at the Magetan District Health Office. Method: This descriptive observational study was conducted at the Magetan District Health Office, utilizing the BPRS method to prioritize health issues. Result: Based on Questionnaire responses revealed Dengue Fever (DBD) as the top-priority problem with a total score of 8633.52. Subsequently, a health problem analysis involved discussions and brainstorming sessions with stakeholders responsible for the DBD program and the Head of the Communicable Diseases Section to identify root causes and plan interventions. Conclusion: Addressing DBD mortality rates requires several interventions, such as enhancing the effectiveness of health education methods using appropriate media for the community, providing SIARVI training to DBD program personnel, and raising early detection awareness among villagers through village authorities. These measures can lead to effective health interventions and improved overall health outcomes.